Cohabitation and roommate bias of symbiotic bacteria in insect hosts - Zytynska, Sharon E. (Mol Ecol, 2019)
Symbiotic interactions between insects and bacteria have long fascinated ecologists. Aphids have emerged as the model system on which to study the effect of endosymbiotic bacteria on their hosts. Aphid‐symbiont interactions are ecologically interesting as aphids host multiple secondary symbionts that can provide broad benefits, such as protection against heat stress or specialist natural enemies (parasitic wasps and entomopathogenic fungi). There are nine common aphid secondary symbionts and individual aphids host on average 1–2 symbionts. A cost‐benefit trade‐off for hosting symbionts is thought to explain why not all aphids host every possible symbiont in a population. Both positive and negative associations between various symbionts occur, and this could happen due to increased costs when cohosting certain combinations or as a consequence of competitive interactions between the symbionts within a host. In this issue of Molecular Ecology, Mathé‐Hubert, Kaech, Hertaeg, Jaenike, and Vorburger (2019) use data on the symbiont status of field‐collected aphids to inform a model on the evolution of symbiont co‐occurrence. They vary the effective female population size as well as the rate of horizontal and maternal transmission to infer the relative impact of symbiont‐symbiont interactions versus random drift. Additional data analysis revisits an association between two symbionts in a fruit fly species using a long‐term data set to highlight that such interactions are not limited to aphids.